Flouting Maxim in External Radio Communication Aboard Vessel - Sri Sartini; Yudhanita Pertiwi (Sekolah Tinggi Maritim Yogyakarta, 2021)
Along with the development of increasingly sophisticated technology, vessels as means of transportation at sea have progressed a lot. There is a part of activities aboard vessel which determines the effectiveness of every voyage of the vessel which is communication aboard vessel. Communication which occurs intensively and properly leads to effective communication. In radio communication committing flouting maxim of conversation could not be avoided. The radio communication context plays significant role to interpret the meaning of the speech itself. This study aims to determine the conversational implicature used aboard vessel and the flouting maxims which arise especially from the external radio communication. The design of the research was descriptive qualitative in which the data were taken from the radio communication among cadet’s radio communication practice in bridge simulator. The finding shows that the four types of maxim flouting were committed by the duty officers on radio communication. The highest maxim flouted was flouting maxim of quantity as much as 36,3%. The less frequent maxim to be flouted was maxim of manner and quality as much as 18,2%. The other 27,3% was the occurrence of flouting maxim of relevance. The rationales behind the flouting maxims were also revealed in this study to get the knowledge and best practices onboard radio communication.